Methods and Techniques Used by English Teacher Educators in Nepal - Bhim Lal Bhandari (Journal La Edusci, 2020)
This qualitative research study aims to explore the methods and techniques used by teacher educators in Nepalese English Language Teaching (ELT) contexts. Four teacher educators from two campuses of Rupandehi district of Nepal were selected purposively. Open-ended questions were used to collect information from the participants. The results of the study reveal that grammar-translation method (GTM), audio-lingual method and communicative language teaching (CLT) were three major methods like-wise, role play, group, and pair work techniques were found to be used frequently used in the ELT classrooms by teacher educators. The study reveals a positive perception of teachers towards the methods and techniques used by them. It also shows the necessity of the eclectic method with the idea that no method or technique is the best and worst in English language teaching.